Memorial de Maria Moura: do romance à minissérie - Alcântara, Lídia Carla Holanda (2016)
The present paper studies Rachel de Queiroz’s narrative entitled Memorial de Maria Moura, published in 1992, and the minisseries inspired in it, which carries the same name, aired in Globo network in 1994. This work studies the transposition from the book to the television and the resources used in this transposition, which bring the written narrative to the television narrative.We also study the paratexts present in both plots, which contribute to the composition of Queiroz’s and Globo’s work as a whole, but not being actually part of the story. For that, this paper was divided in three sections: the first theoretical one, which brings studies abaout literature, television and transposition; the second one which studies paratexts; and the third one, which studies the tansposition from the written story to the television. For that, we used as theoretical resorces Linda Hutcheon, Ana Balogh and Gerard Genette.